Fatores de risco associados à mortalidade neonatal em pacientes internados no serviço de neonatologia do Hospital Infantil Nossa Senhora da Glória/Vitória-ES entre 2002/2005 - Muniz, Virgínia Maria (2006)
The primary objective of this study was to assess major risk factors associated with mortality in infants admitted to the Neonatal Care Unit at the Hospital Infantil Nossa Senhora da Glória, Vitória, Brazil from 2002 to 2005. Using a case-control design; 55 cases (neonatal deaths) and 203 control subjects (infants who survived at least 28 days) were matched by gestational age and year of admission. The assessed variables were categorized as maternal, prenatal and perinatal, neonatal, and hospital care. Differences in categorical variables and trends were compared using the χ 2 and student´s t tests. The risk of mortality was estimated by the Odds Ratio (OR) with 95% confidence intervals (95% CI) using a multiple logistic regression model. A protective effect for mortality was detected when the time of labor was less than 24 hr (OR=0.46, 95% CI = 0.26-0.80). Use of vasoactive drugs and birth weight between 500 and 1.000g were significantly associated with neonatal mortality (OR=33.8, 95% CI=7.02-163.19 and OR=6.60, 95% CI=2.38-18.33, respectively). These risk factors for neonatal mortality should be considered by health professionals in the management of infants in neonatal intensive care units as well as primary care settings.